(Determine the Impact of Public Relations Ethics in Strategic Decisions) Descriptive Analytical Study of a Sample of Administrative Leadership in the Ministry of Higher Education - عبد الجبار منى حيدر (Journal of Economics and Administrative Sciences, 2015)
Role of public relations (PR) and from one community to another, depending on the different cultures of these societies in General, and different ethical values established by their practitioners in these communities organizations , public relations in developed societies, and in some developing countries have taken great strides to contribute to the strategic planning and decision-making, in the framework of their commitment to the values and ethical standards for practitioners, In contrast, we find that applied in Iraq still skips phase coordinate with different communication means with the aim of advertising and publicity for the organization. As a result of the limited recognition of the strategic and vital role that public relations can play in maintaining the reputation and standing of the Organization, also lack of commitment or ignorant practitioners with the moral principles of the profession, weaken its credibility and its vital role in making successful strategic decisions, this research aims to examine the role of ethics in public relations (PR) in the formulation of strategic decisions in the sample search, Which included (64) people from the occupants of managerial positions within the Ministry of Higher Education and Scientific Research, and the research found a set of conclusions, most notably the average perception of the management of organization researched to the importance of the public relations and its moral commitment in the formulation of successful strategic decisions also accept the model of the study and its assumptions in varying varied strength on the level of study variables and its measurements and that are based on it for a number of recommendations, including defining access to senior decision makers in the Organization, and strengthen the advisory role of (PR) practitioners